2023
DOI: 10.3390/v15061386
|View full text |Cite
|
Sign up to set email alerts
|

Viral Loads in Skin Samples of Patients with Monkeypox Virus Infection: A Systematic Review and Meta-Analysis

Abstract: Despite monkeypox (mpox) being a public health emergency, there is limited knowledge about the risk of infectivity from skin viral loads during mpox infection. Thus, the aim of this study was to estimate cutaneous viral loads among mpox patients globally. Several databases, including Cochrane, EBSCOHost, EMBASE, ProQuest, PubMed, Scopus, and Web of Science, and preprint servers were searched concerning skin mpox viral loads in confirmed mpox subjects. In this systematic review and meta-analysis, a total of 331… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 44 publications
(98 reference statements)
0
3
0
Order By: Relevance
“…Due to its clinical presentation, laboratory confirmation plays a discriminatory role in the diagnosis of MPXV. Various other infections can cause skin affection, and dermal samples should be the first choice for testing the presence of MPXV 16 , 17 . As in previously published studies 8 , 12 , 18 , 19 , we indeed found the highest viral loads (median Ct: 21.2, 95% CI 20.5–22.3) in skin samples with MPXV DNA positivity rate > 90% in samples collected during week 1 and near to 90% in those collected during week 2.…”
Section: Discussionmentioning
confidence: 99%
“…Due to its clinical presentation, laboratory confirmation plays a discriminatory role in the diagnosis of MPXV. Various other infections can cause skin affection, and dermal samples should be the first choice for testing the presence of MPXV 16 , 17 . As in previously published studies 8 , 12 , 18 , 19 , we indeed found the highest viral loads (median Ct: 21.2, 95% CI 20.5–22.3) in skin samples with MPXV DNA positivity rate > 90% in samples collected during week 1 and near to 90% in those collected during week 2.…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis estimated the skin viral burden in Mpox patients including 731 out of 790 confirmed Mpox individuals demonstrating that the pooled skin viral load was 21.71 (95% CI: 20.68–22.75) [ 45 ]. This study postulated that the skin is a viral reservoir and that the elevated Mpox viral loads (lower Ct values: a reverse correlation exists between Ct values and viral loads [ 46 ]) in association with a high rate of cutaneous lesions positive for Mpox indicate a potential transmission route via direct contact with skin lesions [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent systematic review and meta-analysis estimated the skin viral burden in Mpox patients including 731 out of 790 confirmed Mpox individuals demonstrating that the pooled skin viral load was 21.71 (95% CI: 20.68–22.75) [ 45 ]. This study postulated that the skin is a viral reservoir and that the elevated Mpox viral loads (lower Ct values: a reverse correlation exists between Ct values and viral loads [ 46 ]) in association with a high rate of cutaneous lesions positive for Mpox indicate a potential transmission route via direct contact with skin lesions [ 45 ]. Our Spanish colleagues demonstrated that specimens from the oropharynx and rectum contained replication-competent viruses, showing other possible sources of infection; however, the viral DNA loads were lower, suggesting that replication-competent viruses were less common in these samples in comparison to those taken from the skin [ 44 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation